Mandarins and martyrs : the church and the Nguyen dynasty in early nineteenth-century Vietnam - Ramsay, Jacob (Stanford University Press, 2008)
Examines the rise of anti-Catholic hostility in early 19th-century Vietnam under the Nguyen dynasty. Focusing on - but not limited to - the Cochinchina region, this study explores grassroots experiences of the religion and the conflict between the Nguyen court and missionaries of the Missions Etrangeres de Paris.